B Cells Negatively Regulate the Establishment of CD49b+T-bet+ Resting Memory T Helper Cells in the Bone Marrow - Hojyo, Shintaro; Sarkander, Jana; Männe, Christian; Mursell, Mathias; Hanazawa, Asami; Zimmel, David; Zhu, Jinfang; Paul, William E.; Fillatreau, Simon; Löhning, Max; Radbruch, Andreas; Tokoyoda, Koji (Frontiers in Immunology, 2016)
During an immune reaction, some antigen-experienced CD4 T cells relocate from secondary lymphoid organs (SLOs) to the bone marrow (BM) in a CD49b-dependent manner and reside and rest there as professional memory CD4 T cells. However, it remains unclear how the precursors of BM memory CD4 T cells are generated in the SLOs. While several studies have so far shown that B cell depletion reduces the persistence of memory CD4 T cells in the spleen, we here show that B cell depletion enhances the establishment of memory CD4 T cells in the BM and that B cell transfer conversely suppresses it. Interestingly, the number of antigen-experienced CD4 T cells in the BM synchronizes the number of CD49b+T-bet+ antigen-experienced CD4 T cells in the spleen. CD49b+T-bet+ antigen-experienced CD4 T cells preferentially localize in the red pulp area of the spleen and the BM in a T-bet-independent manner. We suggest that B cells negatively control the generation of CD49b+T-bet+ precursors of resting memory CD4 T cells in the spleen and may play a role in bifurcation of activated effector and resting memory CD4 T cell lineages.